Screening, Identification, and Whole-Genome Sequencing of Ferulic Acid Esterase-Producing Lactic Acid Bacteria from Sheep Rumen - Mingxin Qiu; Yong Chen; Lei Wang; Luyu Li; Xiao Zhang; Zhuang Ma; Jiancheng Liu (Microorganisms, 2025)
Ferulic acid esterase (FAE) plays an important role in plant fiber degradation by catalyzing the hydrolysis of lignocellulosic structures. FAE-producing lactic acid bacteria (LAB), as potential probiotics, can improve ruminant digestion and gut health. In this study, two LAB strains (Q2 and Q6) with FAE activity were isolated from sheep rumen. Based on 16S rDNA sequencing, they were identified as Lactobacillus mucosae and Streptococcus equinus, respectively. Compared to Q2, Q6 demonstrated higher enzyme production, lactic acid yield, broader carbohydrate utilization, and stronger antimicrobial activity. The whole genome sequencing revealed Q2 and Q6 possess genomes of 2.14 Mbp and 1.95 Mbp, with GC contents of 46.81% and 37.30%, respectively. Q2 and Q6 exhibited the highest average nucleotide identity (ANI) with L. mucosae DSM 13345 (97.30%) and S. equinus ATCC 33317 (97.92%), respectively. The strains harbored 2101 and 1928 predicted genes, including 1984 and 1837 coding sequences (CDSs), respectively. GO enrichment analysis showed the CDSs predominantly associated with membranes (or cells), catalytic activity, and metabolic processes. KEGG analysis revealed both strains enriched in metabolic pathways, with Q6 showing a notably higher number of proteins in the ABC transporters and quorum sensing than Q2. Carbohydrate-active enzymes database (CAZy) profiling identified 75 CAZymes in Q2 and 93 CAZymes in Q6, with each strain containing one novel fae gene. Safety assessment identified 1 and 33 pathogenic genes, along with 2 and 4 putative antimicrobial peptide genes, in Q2 and Q6, respectively. Notably, Q6 carried 12 virulence factor genes. These findings suggest Q2 exhibits a superior safety profile compared to Q6, indicating a higher probability of Q2 being an effective probiotic strain. In conclusion, both LAB strains produce FAE. L. mucosae Q2 demonstrates suitability as a direct-fed probiotic for livestock, while Q6 exhibits potential as a silage inoculant, though comprehensive safety evaluations are required prior to its application.